The Relationship between Crime Prevention Through Environmental Design (CPTED) and Criminal Geography (CG) - Molnár, Jenő István (Magyar Rendészet, 2021)
Knowledge of crime trends and permanent monitoring of criminal acts are the fundamentum of successful crime prevention. The need of searching of structure, dynamic and volume of crime is not new-fangled, as the examination of relationship between spatial distribution of crime and crime prevention through environmental design (CPTED). However, the philosophy of CPTED has changed significantly over the last two decades, with focus on the role of individuals and the communities, their involvement and the need to encourage them to act. How has this paradigm shift changed the relationship between these two areas? How trivial will be in the future to use CPTED tools in those areas, where we detect greater criminal infection?